Positional differences in muscle-to-bone ratio in National Football League players - Dengel, D. R.; Evanoff, N. G. (International Journal of Sports Medicine, 2023)
The purpose of the present study was to examine the muscle-to-bone ratio (MBR) in National Football League (NFL) players. Three hundred and forty-six NFL players had their total body lean, fat and bone masses determined using dual X-ray absorptiometry and were compared to 228 age-matched, healthy male controls. Compared to the control group, NFL players had a significantly lower percent total body fat (17.90±6.92 vs. 22.93±8.96%, p=0.053), but significantly greater total fat mass (19.76±11.29 vs. 17.84±12.11 kg, p<0.0001), lean mass (84.55±8.75 vs. 55.3±11.79 kg, p<0.0001), bone mineral content (4.58±0.45 vs. 2.91±0.67 kg, p<0.0001), and bone mineral density (1.61±0.11 vs. 1.26±0.21 g/cm2, p<0.0001). NFL players had greater arm MBR (17.70±1.47 vs. 16.48±1.88, p<0.0001) than controls; however, both trunk (26.62±2.55 vs. 31.56±4.19, p<0.0001) and total (18.50±1.31 vs. 19.12±1.88, p<0.001) MBR were lower in NFL players. Leg MBR was not significantly different between NFL players and controls (16.72±1.53 vs. 16.85±1.87, p=0.34). When NFL players were categorized by their offensive or defensive position for comparison, no differences in total MBR were observed. However, leg MBR varied greatly among NFL players by position. It is possible that regional differences in MBR in the NFL players may be related to the demands of that position.